World Development Report 1989 : Financial Systems and Development - World Bank (New York: Oxford University Press, 2012)
This is the twelfth in the annual series assessing major development issues. Economic growth rates among the developing countries have varied considerably. The external environment has had an adverse impact on growth, but domestic policies have been more important. Countries striving to adjust their economies have had considerable success reducing external imbalances but less success with internal balance. In the absence of large inflows of foreign capital, countries will need to rely on the mobilization of domestic financial resources. The structure of a country's financial system reflects its economic philosophy; the present financial structure of many developing countries reflects their approach to development in the 1960s and 1970s, an approach that emphasized government intervention in the economy. Today many countries are revising their approach to rely more heavily on the private sector. For the financial sector, this implies a smaller role for government in the allocation of credit, determination of interest rates, and the daily decisionmaking of financial intermediation. Relaxation of these controls calls for an effective system of prudent regulation and supervision. Hence while the objective is an open market, countries should not remove all capital controls until other economic and financial reforms are in place.